Tactics, strategies and outcomes of relationship retailing in Bangladesh - Yasmin, Sanoara; Rabbanee, Fazlul Kabir; Haque, A. K. M. Ahasanul (Society for Business and Social Sciences, 2012)
Relationship marketing creates, maintains and enhances long term customer relationships and leads to winning customer loyalty and retains customers for long time. This paper focuses on different relationship marketing tactics used by the sample retailers’ and explores customers’ views regarding these tactics. It also highlights on different levels of relationship marketing strategies namely -‐ financial bond, social bond and structural bond. The paper pinpoints the outcome of these relational bonds and tests customers’ satisfaction level corresponding to these relational strategies. Among the relationship marketing tactics, preferential treatment and warm interpersonal communication are found to be widely used by the retailers and also appreciated positively by the customers. Tangible reward and Mailing brochures are treated negatively by the customers while Quantity premium and Mailing seasonal greetings card are found not to be practiced widely by the retailers. The study reveals that structural bond is the most effective relational strategies and social bond is the weakest form of tie for establishing relationship between customer and retailers. The study ends with a conclusive finding that out of one unit satisfaction of the customers, relational bonds are responsible for only 0.59 unit of satisfaction and interestingly 0.60 unit of satisfaction can be generated in absence of all these three bonds.